Relationship between sleep quality and study concentration in Post-COVID-19 patients in Malang Raya - Ali Multazam; Muhammad Hafiz; Bayu Prastowo (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Long Coronavirus disease 2019 (COVID-19), also known as post-acute COVID-19 and Post-COVID-19 syndrome, is characterized by signs and symptoms that occur after the acute phase of COVID-19. Long COVID-19 is found in many COVID-19 survivors. Long COVID-19 patients report a wide range of signs and symptoms. They ranged from respiratory disorders to cognitive disorders. During sleep, serum serotonin is released from special cells in the pons and midbrain stem. Serotonin in the brain is believed to provide a sense of calm and have a sleeping effect. Serotonin improves sleep quality and concentration, increasing energy, creating a better mood, and reducing anxiety. Methods: Analytic observational with cross-sectional data. This study's population comprised 49 respondents who were post-COVID-19 patients living in Malang Raya. Data was collected using the Pittsburgh sleep quality index (PSQI) questionnaire to assess sleep quality and the learning concentration questionnaire to assess learning concentration. Results: A p-value of 0.029 showed a significant association between sleep quality and learning concentration. Furthermore, with a score of 0.312, the link between sleep quality and learning concentration is weak. Conclusions: This study finds that there is a link between sleep quality and learning concentration in post-COVID-19 patients, implying that sleep quality has a significant impact on the occurrence of learning concentration abnormalities.